Hypercoagulation and Thrombophilia in Nonalcoholic Fatty Liver Disease: Mechanisms, Human Evidence, Therapeutic Implications, and Preventive Implications - Northup, Patrick G.; Argo, Curtis K.; Shah, Neeral; Caldwell, Stephen H. (Seminars in Liver Disease, 2012)
Nonalcoholic fatty liver disease (NAFLD) is a spectrum of disorders with a high prevalence in the industrialized world. Despite the high prevalence, the etiology and fundamental pathophysiology for the disease process is poorly understood. There is now a growing fund of knowledge suggesting that the ongoing inflammatory state associated with NAFLD leads to a low-level activation of the coagulation system. Although the data supporting this activation of the coagulation system are significant, the link with end-organ disease, mainly cardiovascular disease, is less firm and mostly epidemiological. In this review, we will explore the evidence for and against a hypercoagulable or thrombophilic state in NAFLD. We will examine possible pathophysiologic explanations and mechanisms, human epidemiologic and population-based data, and the possible therapeutic and preventative implications for treatment of thrombophilia in patients with this disease process.
Keywords: Thrombosis; steatohepatitis; coagulopathy; hepatitis; coagulopathy